Empowering Legal Literacy among Emergency Physicians in Malaysia: Insights from the Inaugural Medical Law and Ethics Workshop on Medical Negligence - Hafizah Zainal Abidin; Yang Xiang Yun; Yuhiza Yusof; Adeline Marie Gnanasegaran (College of Emergency Physician Academy of Medicine, 2025)
Non-Indexed Publication